Characterization of CuO-bacterial cellulose nanohybrids fabricated by in-situ and ex-situ impregnation methods. (15th October 2019) - Almasi, Hadi; Mehryar, Laleh; Ghadertaj, Ali
Graphical abstract: Highlights: CuO-BC nanohybrids were prepared by in-situ and ex-situ methods. Well distribution of NPs without agglomeration was achieved by in-situ methods. Crystalline network of BC was preserved after CuO incorporation by all methods. Better CuO release controlling was resulted in sonochemical in-situ method. Antimicrobial activity of ex-situ nanohybrid was higher than in-situ ones. Abstract: The aim of this research was to fabricate CuO-bacterial cellulose (BC) nanohybrids by two in-situ synthesis methods including sonochemical and precipitation methods. The ex-situ synthesized nanohybrid was also prepared by immersing BC pellicles in commercial CuO dispersion. FT-IR analysis confirmed the formation of real nanohybrid by occurring new interactions between CuO-NPs and BC. XRD results approved no disruption effect of nanohybrid formation on the crystallinity index of BC nanofibers. FE-SEM results indicated the formation of small sized NPs attached to the inner space of BC network at in-situ synthesized nanohybrids. But agglomerated NPs precipitated on the surface of BC layer was observed for ex-situ synthesized sample. In spite of higher loading capacity of ex-situ method, the in-situ synthesized nanohybrids exhibited lower release rate of NPs into the water. The antibacterial activity of ex-situ synthesized nanohybrid against S.aureus and E.coli bacteria was more than both of in-situ synthesized samples.